PENGARUH STRUKTUR MODAL, PROFITABILITAS, DAN UKURAN PERUSAHAAN TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN PROPERTY DAN REAL ESTATE YANG TERDAFTAR DI BEI PERIODE 2018-2021 - Hapsari, Martania Dwi; Retnosari, Retnosari (LPPM University 17 Agustus 1945 Samarinda, 2023)
The purpose of this study is to analyze and evaluate the effect of capital structure, profitability, and company size on company value in property and real estate companies listed on the Indonesia Stock Exchange during the 2018-2021 period. The researcher chose to take the capital structure variable to see the entity's ability to manage debt effectively during the study period, the profitability variable to evaluate its impact on the research period, and the company size variable to identify the importance of assets for investors. The data used in this study is secondary data obtained from the www.idx.co.id page by downloading the 2018-2021 financial reports. The population in this study consisted of 81 companies in the property and real estate sector which were listed on the Indonesia Stock Exchange, but only 28 companies were taken as samples using a purposive sampling method. The research method used is a quantitative method with a quantitative descriptive approach. Data were analyzed using multiple linear regression and hypothesis testing assessed from the coefficient of determination, F test, and T test. The results showed that the capital structure proxied by DER had no effect on firm value in property and real estate companies listed on the IDX, the profitability of which was proxied by ROA has no effect on firm value in property and real estate companies listed on the IDX, and company size proxied by Size has an effect on firm value in property and real estate companies listed on the IDX.